(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Two thirds of every Indian lady has relocated for marriage, around 300 million ladies, however little is thought about this tremendous movement. This paper gives a point by point bookkeeping of the puzzlingly enormous relocation of Indian ladies and assesses its causes. As opposed to standard way of thinking, marriage relocation doesn’t add to hazard sharing. Nor is it driven by sex proportion lopsided characteristics. Rather, I present a basic model where guardians must look for a mate for their girl topographically. By including geological inquiry grindings, the model justifies the enormous regional contrasts.